Improving Students Achievement in Writing Hortatory Exposition Text Though Debate Technique - Wahdini, Anisa; Sofian, Sofian; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is about Improving Students’ Achievement in Writing Hortatory Exposition Text through Debate Technique. The purpose of this research is to improve the students’ achievement in writing hortatory exposition text through debate technique. The methodology of this research was a classroom action research which consisted of 2 cycles. The participants of this research were 39 students of class XI IPA 5 of SMA 3 Pontianak in the academic year of 2016/2017. In completing the research, the researcher used the observation checklist table, field note and writing assessment as the instruments of data collecting. By conducting the classroom action research, it was found out that debate technique improved the students’ achievement in writing hortatory exposition text. The result of this research has shown that the students’ progress is improved in each cycle. The mean score of the first cycle is 59.74 (poor to average). In the first cycle some students were not able to develop the ideas and make sentences into a good paragraph. The second cycle is 70 (average to good). In brief, the increasing score proved that debate technique improved the students’ achievement in writing hortatory exposition text.  Keywords: debate technique, writing, hortatory exposition text, classroom action research